Increasing Flexibility and Agility at the National Reconnaissance Office Lessons from Modular Design, Occupational Surprise, and Commercial Research and Development Processes - Baiocchi, Dave (RAND Corporation, 2013)
To help the National Reconnaissance Office (NRO) become more flexible and agile in an increasingly uncertain world, RAND sought answers to two key questions: Would the NRO benefit from building modular satellites? What lessons might be drawn from how chief executive officers, military personnel, and health care professionals (among others) respond to surprise?